Dorsal striatal dopamine D1 receptor availability predicts an instrumental bias in action learning - de Boer, Lieke (Proc Natl Acad Sci U S A, 2019)
Learning to act to obtain reward and inhibit to avoid punishment is easier compared with learning the opposite contingencies. This coupling of action and valence is often thought of as a Pavlovian bias, although recent research has shown it may also emerge through instrumental mechanisms. We measured this learning bias with a rewarded go/no-go task in 60 adults of different ages. Using computational modeling, we characterized the bias as being instrumental. To assess the role of endogenous dopamine (DA) in the expression of this bias, we quantified DA D1 receptor availability using positron emission tomography (PET) with the radioligand [(11)C]SCH23390. Using principal-component analysis on the binding potentials in a number of cortical and striatal regions of interest, we demonstrated that cortical, dorsal striatal, and ventral striatal areas provide independent sources of variance in DA D1 receptor availability. Interindividual variation in the dorsal striatal component was related to the strength of the instrumental bias during learning. These data suggest at least three anatomical sources of variance in DA D1 receptor availability separable using PET in humans, and we provide evidence that human dorsal striatal DA D1 receptors are involved in the modulation of instrumental learning biases.